Functionalising carbon nanotubes. (31st January 2008) - Lynam, C.; Minett, A.I.; Habas, S.E.; Gambhir, S.; Officer, D.L.; Wallace, G.G.
The realisation of efficient functionalisation strategies is critical to the further development of CNT science and technology. The area has attracted a great deal of attention and a host of innovative approaches developed. However, as the examples highlighted here illustrate, many challenges remain.